PENGARUH PENYALURAN DANA ZAKAT, INFAQ, SEDEKAH (ZIS) TEHADAP PERTUMBUHAN EKONOMI DI PROVINSI LAMPUNG - Saputra, Irawan Ferdi Hari; Setyanto, Alief Rakhman (STAI Darul Qalam Tangerang, 2024)
The distribution of zakat, infaq and alms (ZIS) funds is expected to make a positive contribution to economic growth in a region. This study aims to examine the effect of the distribution of ZIS funds on economic growth in Lampung province. The results of the analysis show that the distribution of ZIS funds has a positive and significant effect on economic growth in Lampung province. In particular, zakat and infaq/edekah funds have a positive and significant effect on economic growth, while zakat fitrah has no significant effect. In addition, this study also found that other factors such as population growth, investment, and local government expenditure also have a significant effect on economic growth in Lampung province. the distribution of ZIS funds can make a positive contribution to economic growth in Lampung province. Therefore, efforts are needed to increase public awareness and participation in the distribution of ZIS funds so that the potential contribution of ZIS to economic growth can be maximized.